At the intersection of co‐creation: Exploring LGBTQ2S evaluation with youth. Issue 175 (21st October 2022) - Whynot, Jane; Heath, Sarah; Silver, Larissa; Robin, Charlie‐Rae; Kent, Mathew
Abstract: This article applies a reflective account of experiences of youth, organizational personnel, and evaluators in an evaluation of the Youth Services Bureau of Ottawa's transition to a Housing First for Youth model. A prominent aspect of this evaluation was the extended focus on, to and with LGBTQ2S+ youth. Our collective account positions co‐creation along a continuum involving these youth as data sources, as consultants, co‐evaluators, and as co‐leaders. Authors use these three continuum points to present related theory, application in our project context, the intersectional implications, and lessons learned to highlight practical and theoretical implications for LGBTQ2S+ evaluation. We conclude our contribution to this special issue by discussing implications and elements that need to be considered for LGBTQ2S+ evaluation.